2012
DOI: 10.1016/j.neuropsychologia.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations between types of verbal memory and prefrontal brain structure in healthy aging and late life depression

Abstract: Verbal memory deficits attributed to late life depression (LLD) may result from executive dysfunction that is more detrimental to list-learning than story-based recall when compared to healthy aging. Despite these behavioral dissociations, little work has been done investigating related neuroanatomical dissociations across types of verbal memory performance in LLD. We compared list-learning to story-based memory performance in 24 non-demented individuals with LLD (age~66.1±7.8) and 41 non-demented/non-depresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…Depression had no effect on the performance of tests in which the memory accessed involved verbal narratives or visual stimuli. As other studies have reported contradictory fi ndings (Elderkin- Thompson et al, 2003;Lamar et al, 2012;Nebes et al, 2000), this issue should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Depression had no effect on the performance of tests in which the memory accessed involved verbal narratives or visual stimuli. As other studies have reported contradictory fi ndings (Elderkin- Thompson et al, 2003;Lamar et al, 2012;Nebes et al, 2000), this issue should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, individuals with symptoms of depression, when compared with subjects without these symptoms, performed worse on the list of words, but not on narrative recall. One study has already demonstrated that individuals with depression, compared with subjects without depression, demonstrate greater verbal memory defi cits when the verbal stimuli were presented in the form of word lists; the same result was not observed when verbal stimuli were presented in narrative form, suggesting that this difference might be due to the involvement of different neural areas for the two types of presentation of verbal stimuli (Lamar et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been reported specific effects on verbal memory in late life depression, where recalling list learning items is affected while recalling storytelling is unaffected [65]. Lamar et al [65] compared brain area volumes in late life depression with matched healthy controls, and found a correlation between volume sizes of prefrontal and cingulate sub-regions with poor performance on the list-learning task (California Verbal Learning test, CVLT) in the late life depression group.…”
Section: Learningmentioning
confidence: 99%